1997
DOI: 10.1038/sj.onc.1201296
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of the prenylation of K-Ras, but not H- or N-Ras, is highly resistant to CAAX peptidomimetics and requires both a farnesyltransferase and a geranylgeranyltransferase I inhibitor in human tumor cell lines

Abstract: The farnesyltransferase (FTase) inhibitor FTI-277 is highly e ective at blocking oncogenic H-Ras but not KRas4B processing and signaling. While inhibition of processing and signaling of oncogenic K-Ras4B is more sensitive to the geranylgeranyltransferase I (GGTase I) inhibitor GGTI-286 than it is to FTI-277 in K-Ras4B-transformed NIH3T3 cells, the sensitivity of K-Ras as well as H-and N-Ras to the CAAX peptidomimetics in human tumor cell lines is not known. Here, we report that a panel of ®ve human carcinoma c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
144
2

Year Published

1998
1998
2013
2013

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 217 publications
(153 citation statements)
references
References 8 publications
7
144
2
Order By: Relevance
“…Although FTI-276 was unable to inhibit K-Ras prenylation, it was very e cacious at suppressing tumor growth of both A-549 and Calu-1 cells in the nude mouse xenograft model. Furthermore, FTI-277 (50 mM) inhibited by 70% and 90% the anchorageindependent growth in soft agar of A-549 and Calu-1 cells, respectively (Lerner et al, 1997). Thus, in two models of transformation (nude mouse xenografts and soft agar), inhibition of growth did not require inhibition of oncogenic K-Ras processing.…”
Section: Discussionmentioning
confidence: 86%
“…Although FTI-276 was unable to inhibit K-Ras prenylation, it was very e cacious at suppressing tumor growth of both A-549 and Calu-1 cells in the nude mouse xenograft model. Furthermore, FTI-277 (50 mM) inhibited by 70% and 90% the anchorageindependent growth in soft agar of A-549 and Calu-1 cells, respectively (Lerner et al, 1997). Thus, in two models of transformation (nude mouse xenografts and soft agar), inhibition of growth did not require inhibition of oncogenic K-Ras processing.…”
Section: Discussionmentioning
confidence: 86%
“…Human Pancreatic Nestin Expressing (HPNE) cells were the kind gift of Dr Channing Der and Dr Paul Campbell (University of North Carolina) and were maintained in media containing 3:1 mixture of DMEM and M3F base media (INCELL). NIH-3T3 cells that stably express mutant K-Ras and C7 cells that stably express mutant K-Ras were grown as described by us, 19,20 respectively.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, in vitro and in vivo experiments have shown that K-Ras was geranylgeranylated in cells treated with FTIs (Rowell et al, 1997;Whyte et al, 1997;Sun et al, 1998). Thus, both FTase and GGTase I need to be inhibited to fully block K-Ras isoprenylation (Lerner et al, 1997). Whether inhibition of RhoB farnesylation is involved in the mechanism of action of FTIs is unclear at this time (Lebowitz and Prendergast, 1998;Prendergast, 2001;Sebti and Der, 2003).…”
Section: Introductionmentioning
confidence: 99%